2009
DOI: 10.1016/j.chembiol.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A Promiscuous Ribozyme Promotes Nucleotide Synthesis in Addition to Ribose Chemistry

Abstract: Here we report the in vitro selection of an unusual ribozyme that efficiently performs nucleotide synthesis even though it was selected to perform a distinctly different sugar chemistry. This ribozyme, called pR1, when derivatized with ribose 5-phosphate (PR) at its 3' terminus and incubated with 6-thioguanine, produces two interconverting thiol-containing products corresponding to a Schiff base and its Amadori rearranged product. Consistent with this hypothesis, removing the 2-hydroxyl from the PR substrate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…However, the epigenetic interactions that generated these paths were pleiotropic effects such as increased protein aggregation and reduced thermodynamic stability, in contrast to the cooperativity of RNA mutations in our study, which was probably caused by a single factor, binding to the Rho protein. 2 Other studies found that catalytic promiscuity can help in the evolution of a new function both in proteins (65,66) and in RNAs (67). At present, the most powerful experimental system to study macromolecular evolution appears to be phage-assisted continuous evolution (68).…”
Section: Discussionmentioning
confidence: 99%
“…However, the epigenetic interactions that generated these paths were pleiotropic effects such as increased protein aggregation and reduced thermodynamic stability, in contrast to the cooperativity of RNA mutations in our study, which was probably caused by a single factor, binding to the Rho protein. 2 Other studies found that catalytic promiscuity can help in the evolution of a new function both in proteins (65,66) and in RNAs (67). At present, the most powerful experimental system to study macromolecular evolution appears to be phage-assisted continuous evolution (68).…”
Section: Discussionmentioning
confidence: 99%
“…Small metabolic repertoire and promiscuous ribozymes (e.g. 190 ) were the norm. The invention of the chromosome seems to be the pinnacle of the RNA world, as from its very beginning it was striving for this elusive target (see Section I/3.…”
Section: Iii/2 Enzymatizationmentioning
confidence: 99%
“…Kinase ribozymes 187 could produce the D-ribose-5-phosphate and then 5-phospho-D-ribose-1-diphosphate (PRPP). Ribozymes can catalyse the formation of the glycosidic bond between PRPP and a pyrimidine [188][189][190] or a purine 190,191 nucleobase. Moreover, almost all biologically important reactions could be catalysed by ribozymes to some extent 36 .…”
Section: Iii/2 Enzymatizationmentioning
confidence: 99%
“…Recently we made the interesting discovery that a ribozyme selected for its ability to mediate chemistry between ribose and 6-thioguanosine could also promote purine nucleotide synthesis when the ribose substrate was substituted with PRPP (Lau and Unrau 2009). This promiscuous ribozyme suggests that metabolically relevant ribozymes making use of a small metabolite such as ribose could have easily evolved to promote nucleotide synthesis with PRPP.…”
Section: Abiotic Nucleotide Synthesismentioning
confidence: 99%
“…Given the fundamental importance of this chemistry to modern metabolism and its potential compatibility with abiotic supplies of ribose and nucleobases (Lau and Unrau 2009), the ability of RNA to mediate such chemistry serves as a potential bridge between the abiotic and biotic RNAWorld of nucleotide synthesis. However, the chemistry of glycosidic bond formation presents a number of hurdles for RNA catalysts.…”
Section: Abiotic Nucleotide Synthesismentioning
confidence: 99%